Cyclical Variations in the Duration of Unemployment Spells - Corak, Miles (Relations industrielles / Industrial Relations, 1993)
The purpose of this paper is to examine one implication of the view that the duration of unemployment is invariant over the course of the business cycle. The data used are derived from the Annual Work Patterns Survey for the years 1978-80 and 1982-85. Accelerated life-time models under a variety of distributional assumptions are used to examine unemployment spells from each year of data.